From defense to development? : international perspectives on realizing the peace dividend - Markusen, Ann R.; DiGiovanna, Sean; Leary, Michael C., 1960- (Studies in defence economics (Chur, Switzerland) ;, 2003)
This book tracks the progress of 12 countries on five continents in moving resources from defense to civilian activity in the 1990s. Based on intensive research, it addresses each country with an impressive standard of scholarship.